2004
DOI: 10.1590/s0100-84042004000200017
|View full text |Cite
|
Sign up to set email alerts
|

Poliembrionia e aspectos da embriogênese em Tabebuia ochracea (Chamisso) Standley (Bignoniaceae)

Abstract: -(Polyembryony and aspects of embryogenesis in Tabebuia ochracea (Chamisso) Standley (Bignoniaceae)). The origin of the extranumerary embryos and the embryogeny of Tabebuia ochracea were analysed. Extranumerary apomictic embryos are of adventitious origin from hypostase cells and from the integument of ovule micropilar region. The embryogeny corresponds to Onagrad type. Among 233 dissected seeds, 81.37% presented polyembryony and up to seven embryos were detected in a single seed. Sexual and adventitious embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0
26

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 28 publications
5
37
0
26
Order By: Relevance
“…This result is new to Bignoniaceae, because the neopolyploid species of Anemopaegma and Handroanthus studied to date are clearly self-compatible (Bittencourt & Semir 2005;Bittencourt & Moraes 2010;Firetti-Leggieri et al 2013;Sampaio et al 2013a). As these neopolyploid and self-compatible species also present polyembryony caused by sporophytic apomixis (Costa et al 2004;Bittencourt & Moraes 2010;Sampaio et al 2013b), it is possible that the self-fertility observed was trigged by the development of adventive embryos, as previously hypothesized (Oliveira et al 1992;Bittencourt & Semir 2005;Bittencourt & Moraes 2010;Sampaio et al 2013a). Our data suggests that neopolyploidy does not seem to be the main factor causing self-fertility in Handroanthus species.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This result is new to Bignoniaceae, because the neopolyploid species of Anemopaegma and Handroanthus studied to date are clearly self-compatible (Bittencourt & Semir 2005;Bittencourt & Moraes 2010;Firetti-Leggieri et al 2013;Sampaio et al 2013a). As these neopolyploid and self-compatible species also present polyembryony caused by sporophytic apomixis (Costa et al 2004;Bittencourt & Moraes 2010;Sampaio et al 2013b), it is possible that the self-fertility observed was trigged by the development of adventive embryos, as previously hypothesized (Oliveira et al 1992;Bittencourt & Semir 2005;Bittencourt & Moraes 2010;Sampaio et al 2013a). Our data suggests that neopolyploidy does not seem to be the main factor causing self-fertility in Handroanthus species.…”
Section: Discussionsupporting
confidence: 57%
“…Histological analyses have shown that the supernumerary embryos found in polyembryonic seeds arise from somatic tissues of the ovule in Handroanthus ochraceus (Cham.) Mattos (Costa et al 2004), H. chrysotrichus (Mart. ex DC) Mattos (Bittencourt & Moraes 2010) and Anemopaegma acutifolium DC.…”
Section: Introductionmentioning
confidence: 99%
“…O endosperma periférico diferenciado tardiamente ainda não havia sido reportado para as Bignoniaceae, mas já havia sido (Beltrati & Piccolo 1979;Von Teichman & Van Wyk 1991). As paredes das células da hipóstase, em T. ochracea, apresentam um espessamento péctico e um acúmulo de compostos fenólicos, como verificado para Tabebuia pulcherrima (Bittencourt Júnior & Mariath 2002), entretanto, a presença de lignina é questionada por Costa et al (2004), uma vez que estas células se diferenciam em embriões adventícios, o que gera a necessidade de maiores investigações. Carboidratos diferentes do amido foram verificados nas células da hipóstase em T. ochracea (Costa et al 2004), em Ornithogalum caudatum Aiton (Tilton 1980) e em T. pulcherrima (Bittencourt Júnior & Mariath 2002), podendo estar relacionados com a função nutritiva deste tecido (Tilton 1980).…”
Section: Discussionunclassified
“…Assim, o estudo da ontogenia da semente em T. ochracea, justifica-se pela escassez de estudos sobre ontogenia da semente no gênero, pela importância ecológica e econômica da espécie e, também, por viabilizar comparações com T. chrysotricha, espécie considerada taxonomicamente próxima de T. ochracea (Gentry 1992). T. chrysotricha e T. ochracea ainda representam exceções na família, por apresentarem apomixia e sementes poliembriônicas (Costa et al 2004, Souza et al 2005.…”
unclassified
“…Studies over the last two decades have shown that outbreeding and LSI are common features in many tropical trees (Bawa et al, 1985) but seem to be such common features in the Bignoniaceae that a phylogenetic component has been argued to explain such familial clustering (Gibbs & Bianchi 1999). However, selffertility and apomixis have been also described in some woody tropical Bignoniaceae (Costa et al 2004). The extremely low fruit set from open pollination is consistent with other tropical trees (Bawa et al 1985).…”
Section: Discussionmentioning
confidence: 99%